Analisis Sentimen Positif Terhadap Avoskin sebagai Eco Friendly Brand di Media Sosial X dan TikTok - Magrifatul Zania Maharani (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
. The Indonesian beauty industry continues to grow, marked by the emergence of many local skincare brands. Avoskin is a local skincare brand that is committed to